(untitled) (Nexus International Journal of Science and Education, 2024)
This study aimed to determine the extent of school canteen management as a determinant of service quality of junior high schools in Digos City Division. One hundred (100) junior high school learners participated in this study. The study used the non-experimental quantitative design utilizing the descriptive method of research. The findings revealed that school canteen management was extensive regarding personnel and staff, price and commodities, quality and quantity of food served, services, and canteen sharing. However, wearing white shirts and wearing hairnets was extensive. Healthy choices of foods were sold at competitive prices and were too costly for learners to afford. The high school canteens serve fresh food, and the canteen staff undertakes extensive training to ensure quality and food safety. Moreover, the service quality in tangibility, assurance, reliability, responsiveness, and empathy was moderately extensive. However, indicators of assurance and reliability were less extensive. The canteen staff's positive behavior towards clientele inspired students to patronize their produce, keep service accurately, keep service dependently, and staff being cheerful and kind all the time were less extensive. There was a significant relationship between school canteen management and service quality. School canteen management, in terms of empathy and assurance, significantly influences service quality. School canteens should provide clean and safe food for the learners. The canteen coordinator should plan for team building activities. Deped should conduct more training and workshops for canteen staff.